2004
DOI: 10.1071/ar03112
|View full text |Cite
|
Sign up to set email alerts
|

Screening rhizobacteria for improving the growth, yield, and oil content of canola (Brassica napus L.)

Abstract: One hundred rhizobacteria previously isolated from the rhizospheres of Brassica species were screened for their growth promoting activity in Brassica napus L. under gnotobiotic conditions. Results revealed that 58% of the rhizobacteria increased root length (up to 139%), 39% enhanced shoot length (up to 78%), and shoot weight (up to 72%) of Brassica napus L. Based upon growth promotion of B. napus seedlings under gnotobiotic conditions, 10 promising plant-growth-promoting rhizobacteria (PGPR) were selected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 25 publications
3
36
1
8
Order By: Relevance
“…auxin) and ability to hydrolyze the ACC in plant roots . Asghar et al (2004) reported a 3.5-fold increase in auxin production by rhizobacteria with L-TRP than without L-TRP. It has been reported that other traits, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…auxin) and ability to hydrolyze the ACC in plant roots . Asghar et al (2004) reported a 3.5-fold increase in auxin production by rhizobacteria with L-TRP than without L-TRP. It has been reported that other traits, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A strain of Bacillus cereus UW85 has previously been reported to suppress plant diseases caused by Oomycetes (Silo-Suh et al, 1994 andStabb, 1996) due to the production of the antibiotics Zwittermicine (Milner et al, 1996a) and Kanosamine (Milner et al, 1996b). Indirect promotion of plant growth occurs when PGPR lessen or prevent the deleterious effects of phytopathogens through mechanisms such as antibiosis against the pathogens (Asghar et al, 2004). Elizabeth and Handelsman (1999) suggested that the effect of Bacillus cereus on the microbial community in the rhizosphere is perhaps exerted by stimulating growth of other bacteria that stimulate root growth, antagonize the pathogen or induce resistance in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of biological control of plant pathogens by fluorescent pseudomonads generally involve production of bacterial metabolites such as siderophores, hydrogen cyanide, extra cellular lytic enzymes and induced systemic resistance (O,Sullivan and O,Gara, 1992). Furthermore, Flavobacterium is an efficient rhizosphere genus in promotion of plant growth (Asghar et al, 2004). Nevertheless, to our knowledge, no report has been published on biological control ability of this genus.…”
Section: Introductionmentioning
confidence: 76%